Polycystic ovary syndrome: a comprehensive review of pathophysiology, diagnosis, and emerging management strategies - Bashir, Mustafa; Amin, Fiza; Amin, Huda; Teli, Toufeeq Ahmed; Tali, Tavseef Ahmad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder affecting 6-20% of women of reproductive age, characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. Its pathophysiology involves intricate interactions among genetic, epigenetic, metabolic, and environmental factors, with insulin resistance, gut microbiota dysbiosis, and novel biomarkers like anti-Müllerian hormone (AMH) playing pivotal roles. This review provides an in-depth exploration of PCOS etiology, diagnostic challenges, and management strategies, including lifestyle interventions, pharmacological therapies, and emerging approaches like microbiota modulation and microRNA therapies. We also address long-term health risks, such as cardiovascular disease, type 2 diabetes mellitus (T2DM), and mental health challenges, emphasizing personalized and multidisciplinary treatment strategies.